All‐Amorphous Junction Field‐Effect Transistors Based on High‐Mobility Zinc Oxynitride. (18th March 2021) - Reinhardt, Anna; von Wenckstern, Holger; Grundmann, Marius
Abstract: This report is on the electrical properties of all‐amorphous junction field‐effect transistors (JFETs) based on n ‐type zinc oxynitride (ZnON) as a channel material and room‐temperature deposited p ‐type ZnCo2 O4 (ZCO) as a heterojunction gate. Devices with different channel thicknesses are thereby compared. Best devices with 48 nm channel layer thickness achieve drain current on/off –ratios of 10 5 and low subthreshold swing of 134 mV dec −1 within a gate voltage sweep of less than 2 V. The channel mobility extraction is reliable for 90 nm‐thick channels yielding saturation mobility values over 50 cm 2 V −1 s −1 . For JFETs with 48 nm‐thick channels an overestimation of the saturation mobility due to deviations from the ideal transistor characteristics is determined. Abstract : Fully amorphous junction field‐effect transistors based on n‐type zinc oxynitride as channel material and p‐type zinc‐cobalt‐oxide as gate electrode are presented. The investigated p‐n heterojunction gate diode provides thin‐film transistors with remarkable switching properties: near‐zero turn‐on voltage, low subthreshold swing of 134 mV dec −1, and high saturation mobility of about 50 cm 2 V −1 s −1, which render them interesting for low‐cost, sustainable electronic devices.